2020
DOI: 10.3389/fonc.2020.01304
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Physical Status From Diagnosis to the End of First-Line Treatment in Breast, Lung, and Colorectal Cancer Patients: The PROTECT-01 Cohort Study Protocol

Abstract: Background: Cancer cachexia and exacerbated fatigue represent two hallmarks in cancer patients, negatively impacting their exercise tolerance and ultimately their quality of life. However, the characterization of patients' physical status and exercise tolerance and, most importantly, their evolution throughout cancer treatment may represent the first step in efficiently counteracting their development with prescribed and tailored exercise training. In this context, the aim of the PROTECT-01 study wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Whereas most studies investigating the influence of physical activity in breast cancer patients focus on specific activities for three months or less, the BEGYN study will quantify the daily physical activity and cardiorespiratory fitness of breast cancer patients based on objective measurements in the context of the oncological therapy for 12 months after diagnosis. Multiple studies have shown that physical activity can have positive effects in breast cancer patients ( 4 6 , 33 35 , 37 ). Guidelines recommend physical activity during breast cancer treatment, in example in the United States ( 102 ), in Great Britain ( 103 ), in Germany ( 39 ) and others.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Whereas most studies investigating the influence of physical activity in breast cancer patients focus on specific activities for three months or less, the BEGYN study will quantify the daily physical activity and cardiorespiratory fitness of breast cancer patients based on objective measurements in the context of the oncological therapy for 12 months after diagnosis. Multiple studies have shown that physical activity can have positive effects in breast cancer patients ( 4 6 , 33 35 , 37 ). Guidelines recommend physical activity during breast cancer treatment, in example in the United States ( 102 ), in Great Britain ( 103 ), in Germany ( 39 ) and others.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the BEGYN study is one of the largest studies with a very broad approach in breast cancer patients that will allow to identify associations between physical, psychological and laboratory variables, thus linking aspects that are often studied separately in breast cancer patients. Regarding the assessment of physical activity, it will be of particular interest to discuss the results of the BEGYN study in the light of other ongoing highly innovative studies such as the PROTECT study which also includes patients with colorectal cancer and lung cancer ( 6 ). One of the major strengths is the continuous recording of the patient’s physical activity and well-being by diary and by use of a fitness tracker since physical activity encompasses not only explicit sports activities, which may last a few hours per week, but also activity during everyday activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, neoadjuvant and adjuvant chemotherapies are extensively used in breast cancer patients to reduce tumor development and improve disease-free survival, but also leads to severe off-target side-effects ( Maughan et al, 2010 ; Redden and Fuhrman, 2013 ; Fisusi and Akala, 2019 ; Schirrmacher, 2019 ). Among these treatment-related side effects, both pre-clinical and clinical studies highlighted that chemotherapeutic agents result in major skeletal muscle deconditioning and, together with exacerbated fatigue, are part of a vicious cycle which negatively impacts their quality of life ( Berger et al, 2015 ; Caan et al, 2018 ; Aleixo et al, 2019 ; Cespedes Feliciano et al, 2019 ; Hiensch et al, 2019 ; Mallard et al, 2020 ). Although breast cancer represents the most deadly female cancer, 5-year survival rate is over 90% ( National Cancer Institute, Surveillance, Epidemiology, and End Result program, 2019 ) emphasizing the critical need to fight long-lasting effects observed in survivors such as skeletal muscle deconditioning.…”
Section: Introductionmentioning
confidence: 99%